Optical fiber and method of making an optical fiber
Patent Information
- Application Number
- CN202611208507.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-10
- Publication Date
- 2026-10-13
AI Technical Summary
[0003]本申请提供光纤及光纤制备方法,以解决小尺寸光纤的强度较弱的问题
[0014]本申请的光纤,通过在多个下陷层的内侧设置第一过渡层和第二过渡层,并在多个下陷层的外侧设置第三过渡层,通过各个过渡层内的碱金属、金属离子以及氟元素的供掺有效缓和了不同层级之间的黏度差,并通过各个过渡层之间的相对折射率差的设置使各个层级之间的粘度更加匹配,减少了光纤预制棒在熔融过程中因为黏度差异导致的内应力的形成以及对光纤强度的影响。
Smart Images

Figure CN122902000A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of optical fiber technology, and in particular to an optical fiber and a method for preparing the optical fiber. Background Technology
[0002] As the application of fiber optic cables in indoor environments becomes more widespread, the demand for small-sized optical fibers is gradually increasing. These small-sized optical fibers have a diameter of 180 to 200 μm after coating. Their small diameter leads to weaker strength, and the fiber optic cables are prone to frequent bending due to the complex cabling environment when being installed indoors, which affects their normal communication. Summary of the Invention
[0003] This application provides optical fibers and methods for fabricating optical fibers to solve the problem of weak strength in small-sized optical fibers.
[0004] This application provides an optical fiber, comprising a core layer, a cladding layer, and a coating layer arranged sequentially from the inside out. The cladding layer includes a first transition layer, a second transition layer, a plurality of recessed layers, a third transition layer, and an outer cladding layer arranged sequentially from the inside out. The relative refractive index of the first transition layer near the core layer is set as Δn2, and the relative refractive index of the first transition layer near the second transition layer is set as Δn3, where Δn2 ≥ Δn3. The relative refractive index of the second transition layer decreases with increasing radius, and the relative refractive index of the third transition layer increases with increasing radius.
[0005] In one possible implementation, the relative refractive index difference Δn1 of the core layer ranges from 0.28% to 0.6%. The numerical range of Δn2 is 0 to 0.25%, and the numerical range of Δn3 is 0% to 0.18%.
[0006] In one possible implementation, the core layer has a radius of 4 μm to 5.2 μm, the first transition layer has a thickness of 2 μm to 3.5 μm, the second transition layer has a thickness of 1.5 μm to 4.5 μm, and the third transition layer has a thickness of 2.5 μm to 4.5 μm.
[0007] In one possible implementation, the material composition of the core layer is as follows: SiO2:GeO2:F:K=(1-a1-b1-c1):a1:b1:c1, where the value of a1 ranges from 0.4% to 1.8%, the value of b1 ranges from 0.05% to 0.3%, and the value of c1 ranges from 0.05% to 0.2%. The material composition of the first transition layer is as follows: SiO2:GeO2:F:K=(1-a2-b2-c2):a2:b2:c2, where the value of a2 ranges from 0.08% to 0.15%, the value of b2 ranges from 0.05% to 0.15%, and the value of c2 ranges from 0 to 0.2%.
[0008] In one possible implementation, the plurality of sunken layers include a first sunken layer, a second sunken layer, and a third sunken layer arranged sequentially from the inside out; The relative refractive index difference Δn4 of the first depressed layer ranges from -0.2% to -0.35%. The relative refractive index difference Δn5 of the second sunken layer ranges from -0.15% to -0.21%. The relative refractive index difference Δn6 of the third sunken layer ranges from -0.3% to -0.45%, and Δn6 ≤ Δn4.
[0009] In one possible implementation, the material ratio of the second transition layer at Δn4 is SiO2:F=(1-a3):a3, where the value of a3 ranges from 0.5% to 1.2%.
[0010] In one possible implementation, the thickness of the first depression layer is 4.5 μm to 8 μm; the thickness of the second depression layer is 3 μm to 6.5 μm; and the thickness of the third depression layer is 4.2 μm to 9 μm.
[0011] In one possible implementation, the coating layer comprises an inner coating layer and an outer coating layer arranged sequentially from the inside to the outside, wherein the ratio of the thickness D1 of the inner coating layer to the thickness D2 of the outer coating layer is D1:D2 = (0.6 to 0.95):1.
[0012] In one possible implementation, when the fiber size is 180 μm, the fiber strength is ≥150 kpsi, and when the fiber bending radius is 5 mm, the bending loss at 1550 nm is ≤0.1 dB.
[0013] This application also provides a method for fabricating optical fibers, the method comprising the following steps: Provide an optical fiber preform corresponding to the optical fiber, the optical fiber preform comprising, from the inside out, a core layer, a first transition layer, a second transition layer, multiple recessed layers, a third transition layer and an outer cladding layer; The optical fiber preform is melted to form an optical fiber transition body; The surface of the optical fiber transition body is vertically heated to ensure that the surface temperature T1 of the optical fiber transition body is between 100°C and 350°C. The optical fiber transition body, after vertical surface heating, is coated. The temperature T2 of the coating environment is lower than the surface temperature T1 of the optical fiber transition body, and the difference between T2 and T1 is 50°C to 200°C. The coated fiber transition body is then cured to obtain the optical fiber.
[0014] The optical fiber of this application, by setting a first transition layer and a second transition layer inside multiple recessed layers and a third transition layer outside multiple recessed layers, effectively mitigates the viscosity difference between different layers through the supply and doping of alkali metals, metal ions and fluorine elements in each transition layer, and makes the viscosity between each layer more matched by setting the relative refractive index difference between each transition layer, thereby reducing the formation of internal stress caused by viscosity differences during the melting process of the optical fiber preform and the impact on the strength of the optical fiber. Attached Figure Description
[0015] Figure 1 This is a schematic diagram of the structure of the optical fiber of this application in one embodiment.
[0016] Figure 2 This is a schematic diagram showing the relationship between the radius and the relative refractive index difference of the optical fiber in one embodiment of this application.
[0017] Figure 3 This is a schematic flowchart of the optical fiber fabrication method of this application in one embodiment.
[0018] Explanation of key component symbols: 100, optical fiber; 200, optical fiber fabrication method; 10, core layer; 20, cladding; 21, first transition layer; 22, second transition layer; 23, recessed layer; 23a, first recessed layer; 23b, second recessed layer; 23c, third recessed layer; 24, third transition layer; 25, outer cladding; 30, coating layer; 31, inner coating layer; 32, outer coating layer.
[0019] The following detailed description, in conjunction with the accompanying drawings, will further illustrate this application. Detailed Implementation
[0020] The following description will refer to the accompanying drawings to provide a more complete picture of the present application. The drawings illustrate exemplary embodiments of the present application. However, the present application may be implemented in many different forms and should not be construed as limited to the exemplary embodiments set forth herein. These exemplary embodiments are provided to make the present application thorough and complete, and to fully convey the scope of the present application to those skilled in the art. The same reference numerals denote the same or similar components.
[0021] The terminology used herein is for the purpose of describing particular exemplary embodiments only and is not intended to limit the application. As used herein, unless the context clearly indicates otherwise, the singular forms “a,” “an,” and “the” are intended to also include the plural forms. Furthermore, when used herein, “comprising” and / or “including” and / or “having,” integers, steps, operations, components, and / or components, but does not exclude the presence or addition of one or more other features, regions, integers, steps, operations, components, and / or groups thereof.
[0022] Unless otherwise defined, all terms used herein (including technical and scientific terms) have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains. Furthermore, unless expressly defined herein, terms such as those defined in a general dictionary should be interpreted as having the same meaning as they have in the relevant art and in the content of this application, and will not be interpreted as having an idealized or overly formal meaning.
[0023] The specific embodiments of this application will be further described in detail below with reference to the accompanying drawings.
[0024] like Figure 1 and Figure 2 As shown, this embodiment provides an optical fiber 100, including a core layer 10, a cladding layer 20, and a coating layer 30 arranged sequentially from the inside out. The cladding layer 20 includes a first transition layer 21, a second transition layer 22, a plurality of recessed layers 23, a third transition layer 24, and an outer cladding layer 25 arranged sequentially from the inside out.
[0025] The relative refractive index of the first transition layer 21 near the core layer 10 is set as Δn2, and the relative refractive index of the first transition layer 21 near the second transition layer 22 is set as Δn3, where Δn2 ≥ Δn3. The relative refractive index of the second transition layer 22 decreases with increasing radius, and the relative refractive index of the third transition layer 24 increases with increasing radius.
[0026] Thus, the optical fiber 100 of this application, by providing a first transition layer 21 and a second transition layer 22 on the inner side of multiple recessed layers 23, and a third transition layer 24 on the outer side of multiple recessed layers 23, effectively mitigates the viscosity difference between different layers through the supply and doping of alkali metals, metal ions and fluorine elements in each transition layer, and makes the viscosity between each layer more matched by setting the relative refractive index difference between each transition layer, thereby reducing the formation of internal stress caused by viscosity differences during the melting process of the optical fiber preform and the impact on the strength of the optical fiber 100.
[0027] In this embodiment, the radius of the core layer 10 ranges from 0 to r1, and the radius of the core layer 10 is from 4 μm to 5.2 μm. The relative refractive index difference Δn1 of the core layer 10 ranges from 0.28% to 0.6%.
[0028] The material composition of the core layer 10 is: SiO2:GeO2:F:K=(1-a1-b1-c1):a1:b1:c1, where the value of a1 ranges from 0.4% to 1.8%, the value of b1 ranges from 0.05% to 0.3%, and the value of c1 ranges from 0.05% to 0.2%.
[0029] It is understood that the radius of the core layer 10 can be 4.0μm, 4.1μm, 4.2μm, 4.3μm, 4.4μm, 4.5μm, 4.6μm, 4.7μm, 4.8μm, 4.9μm, 5.0μm, 5.1μm, 5.2μm, etc., but is not limited to the values listed above. Other unlisted values within this range are also within the scope of protection of this application.
[0030] It is understood that the relative refractive index difference Δn1 of the core layer 10 can specifically be 0.28%, 0.29%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, etc., but is not limited to the values listed above. Other unlisted values within this range are also within the scope of protection of this application.
[0031] It is understood that the value of a1 can be 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, etc., but is not limited to the values listed above. Other unlisted values within this range are also within the scope of protection of this application.
[0032] It is understood that the value of b1 can be 0.05%, 0.10%, 0.15%, 0.20%, 0.25%, 0.30%, etc., but is not limited to the values listed above. Other unlisted values within this range are also within the scope of protection of this application.
[0033] It is understood that the value of c1 can be 0.05%, 0.10%, 0.15%, 0.20%, etc., but is not limited to the values listed above. Other unlisted values within this range are also within the scope of protection of this application.
[0034] In this embodiment, the radius of the first transition layer 21 ranges from r1 to r2, and the thickness of the first transition layer 21 ranges from 2 μm to 3.5 μm. The value of Δn2 ranges from 0 to 0.25%, and the value of Δn3 ranges from 0% to 0.18%.
[0035] It is understood that the thickness of the first transition layer 21 may be 2.0μm, 2.1μm, 2.2μm, 2.3μm, 2.4μm, 2.5μm, 2.6μm, 2.7μm, 2.8μm, 2.9μm, 3.0μm, 3.1μm, 3.2μm, 3.3μm, 3.4μm, 3.5μm, etc., but is not limited to the values listed above. Other unlisted values within this range are also within the scope of protection of this application.
[0036] It is understood that the specific value of Δn2 can be 0.00%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, etc., but is not limited to the values listed above. Other unlisted values within this range are also within the scope of protection of this application.
[0037] It is understood that the specific value of Δn3 can be 0.00%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, etc., but is not limited to the values listed above. Other unlisted values within this range are also within the scope of protection of this application.
[0038] In this embodiment, the material composition of the first transition layer 21 is as follows: SiO2:GeO2:F:K=(1-a2-b2-c2):a2:b2:c2, where the value of a2 ranges from 0.08% to 0.15%, the value of b2 ranges from 0.05% to 0.15%, and the value of c2 ranges from 0 to 0.2%.
[0039] It is understood that the value of a2 can be 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, etc., but is not limited to the values listed above. Other unlisted values within this range are also within the scope of protection of this application.
[0040] It is understood that the value of b2 can be 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, etc., but is not limited to the values listed above. Other unlisted values within this range are also within the scope of protection of this application.
[0041] It is understood that the value of c2 can be 0.00%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, etc., but is not limited to the values listed above. Other unlisted values within this range are also within the scope of protection of this application.
[0042] Furthermore, in the first transition layer 21, the relative refractive index difference Δn at any point is: Where r is the radius of the position corresponding to Δn.
[0043] In this embodiment, the radius of the second transition layer 22 ranges from r2 to r3, and the thickness of the second transition layer 22 ranges from 1.5 μm to 4.5 μm. The second transition layer 22 has a minimum relative refractive index difference Δn4 at r3, and the value of Δn4 ranges from -0.2% to -0.35%. Furthermore, the material composition of the second transition layer 22 at Δn4 is SiO2:F = (1-a3):a3, where the value of a3 ranges from 0.5% to 1.2%.
[0044] The material composition of the second transition layer 22, excluding Δn4, is SiO2:GeO2:F:K=(1-a8-b8-c8):a8:b8:c8, where a8 ranges from 0.15% to 0.08%, b8 ranges from 0.5% to 1.2%, and c8 ranges from 0 to 0.2%.
[0045] It is understood that the thickness of the second transition layer 22 can be 1.5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm, 2.0μm, 2.1μm, 2.2μm, 2.3μm, 2.4μm, 2.5μm, 2.6μm, 2.7μm, 2.8μm, 2.9μm, 3.0μm, 3.1μm, 3.2μm, 3.3μm, 3.4μm, 3.5μm, 3.6μm, 3.7μm, 3.8μm, 3.9μm, 4.0μm, 4.1μm, 4.2μm, 4.3μm, 4.4μm, 4.5μm, etc., but is not limited to the values listed above. Other unlisted values within this range are also within the scope of protection of this application.
[0046] It is understood that the specific value of Δn4 can be -0.20%, -0.21%, -0.22%, -0.23%, -0.24%, -0.25%, -0.26%, -0.27%, -0.28%, -0.29%, -0.30%, -0.31%, -0.32%, -0.33%, -0.34%, -0.35%, etc., but is not limited to the values listed above. Other unlisted values within this range are also within the scope of protection of this application.
[0047] It is understood that the value of a3 can be 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, etc., but is not limited to the values listed above. Other unlisted values within this range are also within the scope of protection of this application.
[0048] like Figure 2 As shown, the relative refractive index difference at various locations of the second transition layer 22 decreases linearly with increasing radius. It is understood that in other embodiments, the relative refractive index difference at various locations of the second transition layer 22 may decrease in other ways with increasing radius, and is not limited to the linear decrease described above.
[0049] In this embodiment, the plurality of sunken layers 23 include a first sunken layer 23a, a second sunken layer 23b, and a third sunken layer 23c arranged sequentially from the inside to the outside. That is, the first sunken layer 23a is disposed on the outer periphery of the second transition layer 22, and the third sunken layer 23c is disposed on the inner periphery of the third transition layer 24.
[0050] The relative refractive index difference of the first depressed layer 23a is Δn4, with a value ranging from -0.2% to -0.35%. The relative refractive index difference of the second depressed layer 23b is Δn5, with a value ranging from -0.15% to -0.21%. The relative refractive index difference of the third depressed layer 23c is Δn6, with a value ranging from -0.3% to -0.45%, and Δn6 ≤ Δn4. This design ensures that the core transmission mode of the optical fiber 100 will not convert to a leaky mode and cause energy loss when the fiber 100 is bent at a small radius.
[0051] It is understood that the specific value of Δn4 can be -0.20%, -0.21%, -0.22%, -0.23%, -0.24%, -0.25%, -0.26%, -0.27%, -0.28%, -0.29%, -0.30%, -0.31%, -0.32%, -0.33%, -0.34%, -0.35%, etc., but is not limited to the values listed above. Other unlisted values within this range are also within the scope of protection of this application.
[0052] It is understood that the specific value of Δn5 can be -0.15%, -0.16%, -0.17%, -0.18%, -0.19%, -0.20%, -0.21%, etc., but is not limited to the values listed above. Other unlisted values within this range are also within the scope of protection of this application.
[0053] It is understood that the specific value of Δn6 can be -0.30%, -0.31%, -0.32%, -0.33%, -0.34%, -0.35%, -0.36%, -0.37%, -0.38%, -0.39%, -0.40%, -0.41%, -0.42%, -0.43%, -0.44%, -0.45%, etc., but is not limited to the values listed above. Other unlisted values within this range are also within the scope of protection of this application.
[0054] In this embodiment, the radius of the first sunken layer 23a ranges from r3 to r4, and the thickness of the first sunken layer 23a ranges from 4.5 μm to 8 μm. The material ratio of the first sunken layer 23a is SiO2:F=(1-a4):a4, where the value of a4 ranges from 0.5% to 1.2%.
[0055] It is understandable that the specific thickness of the first sunken layer 23a can be 4.5μm, 4.6μm, 4.7μm, 4.8μm, 4.9μm, 5.0μm, 5.1μm, 5.2μm, 5.3μm, 5.4μm, 5.5μm, 5.6μm, 5.7μm, 5.8μm, 5.9μm, 6.0μm, 6.1μm, 6.2μm, 6.3μm, 6... The range of micrometers includes 0.4μm, 6.5μm, 6.6μm, 6.7μm, 6.8μm, 6.9μm, 7.0μm, 7.1μm, 7.2μm, 7.3μm, 7.4μm, 7.5μm, 7.6μm, 7.7μm, 7.8μm, 7.9μm, and 8.0μm, but is not limited to the values listed above. Other unlisted values within this range are also within the scope of protection of this application.
[0056] In this embodiment, the radius of the second sunken layer 23b ranges from r4 to r5, and the thickness of the second sunken layer 23b ranges from 3 μm to 6.5 μm. The material composition of the second sunken layer 23b is SiO2:F:GeO2=(1-a5-b5):a5:b5, where a5 ranges from 0.2% to 0.8%, and b5 ranges from 0.05% to 0.1%.
[0057] It is understandable that the specific thickness of the second sunken layer 23b can be 3.0 μm, 3.1 μm, 3.2 μm, 3.3 μm, 3.4 μm, 3.5 μm, 3.6 μm, 3.7 μm, 3.8 μm, 3.9 μm, 4.0 μm, 4.1 μm, 4.2 μm, 4.3 μm, 4.4 μm, 4.5 μm, 4.6 μm, 4.7 μm, 4.8 μm, 4... The range of micrometers includes 0.9 μm, 5.0 μm, 5.1 μm, 5.2 μm, 5.3 μm, 5.4 μm, 5.5 μm, 5.6 μm, 5.7 μm, 5.8 μm, 5.9 μm, 6.0 μm, 6.1 μm, 6.2 μm, 6.3 μm, 6.4 μm, and 6.5 μm, but is not limited to the values listed above. Other unlisted values within this range are also within the scope of protection of this application.
[0058] In this embodiment, the radius of the third sunken layer 23c ranges from r5 to r6, and the thickness of the third sunken layer 23c ranges from 4.2 μm to 9 μm. The material ratio of the third sunken layer 23c is SiO2:F=(1-a6):a6, where the value of a6 ranges from 0.8% to 1.6%.
[0059] It is understandable that the specific thickness of the third sunken layer 23c could be 4.2μm, 4.3μm, 4.4μm, 4.5μm, 4.6μm, 4.7μm, 4.8μm, 4.9μm, 5.0μm, 5.1μm, 5.2μm, 5.3μm, 5.4μm, 5.5μm, 5.6μm, 5.7μm, 5.8μm, 5.9μm, 6.0μm, 6.1μm, 6.2μm, 6.3μm, 6.4μm, 6.5μm, 6.6μm, or 6.7μm. μm, 6.8 μm, 6.9 μm, 7.0 μm, 7.1 μm, 7.2 μm, 7.3 μm, 7.4 μm, 7.5 μm, 7.6 μm, 7.7 μm, 7.8 μm, 7.9 μm, 8.0 μm, 8.1 μm, 8.2 μm, 8.3 μm, 8.4 μm, 8.5 μm, 8.6 μm, 8.7 μm, 8.8 μm, 8.9 μm, 9.0 μm, etc., but not limited to the values listed above. Other unlisted values within this range are also within the scope of protection of this application.
[0060] In this embodiment, the radius of the third transition layer 24 ranges from r6 to r7, and the thickness of the third transition layer 24 ranges from 2.5 μm to 4.5 μm.
[0061] It is understood that the thickness of the third transition layer 24 can be 2.5μm, 2.6μm, 2.7μm, 2.8μm, 2.9μm, 3.0μm, 3.1μm, 3.2μm, 3.3μm, 3.4μm, 3.5μm, 3.6μm, 3.7μm, 3.8μm, 3.9μm, 4.0μm, 4.1μm, 4.2μm, 4.3μm, 4.4μm, 4.5μm, etc., but is not limited to the values listed above. Other unlisted values within this range are also within the scope of protection of this application.
[0062] Furthermore, the relative refractive index difference Δn7 of the third transition layer 24 near the end of the outer cladding layer 25 is 0.
[0063] Furthermore, in the third transition layer 24, the relative refractive index difference Δn at any point is: Where r is the radius of the point corresponding to Δn.
[0064] In this embodiment, the material ratio of the third transition layer 24 is SiO2:F=(1-a7):a7, where the value of a7 ranges from 0 to 1.6%.
[0065] In this embodiment, the radius of the outer cladding layer 25 ranges from r7 to r8, and the value of r8 ranges from 62 μm to 63 μm. The outer cladding layer 25 is pure silicon.
[0066] It is understood that the specific value of r8 can be 62.0μm, 62.1μm, 62.2μm, 62.3μm, 62.4μm, 62.5μm, 62.6μm, 62.7μm, 62.8μm, 62.9μm, 63.0μm, etc., but is not limited to the values listed above. Other unlisted values within this range are also within the scope of protection of this application.
[0067] In this embodiment, the coating layer 30 includes an inner coating layer 31 and an outer coating layer 32 arranged sequentially from the inside to the outside. The ratio of the thickness D1 of the inner coating layer 31 to the thickness D2 of the outer coating layer 32 is D1:D2 = (0.6 to 0.95):1. Both the inner coating layer 31 and the outer coating layer 32 are made of polyacrylate material.
[0068] For the inner coating 31, its elastic modulus is ≤0.7 MPa, the coating viscosity at 25°C is (1500 to 6000) mPa•s, and the density is (0.95 to 1.3) g / cm³. 3 The elongation at break must be ≥150%, and the inner coating must contain at least 0.5% of modifiers and adhesion promoters such as silane coupling agents.
[0069] For the outer coating 32, its elastic modulus is ≥750 MPa, the viscosity at 25°C is (3000 to 8000) mPa•s, and the density is (0.95 to 1.3) g / cm³. 3 Elongation at break ≥10%.
[0070] Furthermore, after the outer cladding 25 is coated with the inner coating 31, the overall size of the optical fiber 100 is 140 μm to 155 μm. After the inner coating 31 is coated with the outer coating 32, the overall size of the optical fiber 100 is 175 μm to 190 μm.
[0071] It is worth noting that after the inner coating 31 and outer coating 32 are applied, when the fiber 100 has a size of 180 μm, the strength of the fiber 100 is ≥150 kpsi, and the bending resistance of the fiber 100 reaches the G657B3 level. The minimum size of existing fibers 100 reaching the G657B3 level is 245 μm, indicating that the performance of this application is far superior to that of existing fibers 100.
[0072] like Figure 3 As shown, this embodiment also provides an optical fiber fabrication method 200 for fabricating the aforementioned optical fiber 100. The optical fiber fabrication method 200 includes the following steps: S1. Provide an optical fiber preform corresponding to optical fiber 100. The optical fiber preform includes a core layer 10, a first transition layer 21, a second transition layer 22, multiple recessed layers 23, a third transition layer 24 and an outer cladding layer 25 arranged sequentially from the inside to the outside. S2. The optical fiber preform is melted to form an optical fiber transition body; S3. Perform vertical surface heating on the fiber transition body to ensure that the surface temperature T1 of the fiber transition body is 100℃ to 350℃. S4. Coating the fiber transition body after vertical surface heating is completed. The temperature T2 of the coating environment is less than the surface temperature T1 of the fiber transition body, and the difference between T2 and T1 is 50℃ to 200℃. S5. Curing the coated fiber transition body to obtain fiber 100.
[0073] For step S1, the material ratio and thickness of each layer of the optical fiber preform correspond to the corresponding layer of the optical fiber 100.
[0074] For step S2, during the melting process of the optical fiber preform, the preform is fed into a heating device such as a drawing furnace for melting. The melting temperature is 1700℃ to 2200℃, and the drawing furnace is filled with an inert gas as a protective gas. The inert gas is either argon or helium, or a mixture of both. When the inert gas is a mixture of argon and helium, the argon content is not less than 50%, and in the protective gas environment composed of the mixed gas, the oxygen content is ≤100ppm, and the optical fiber drawing speed is ≥50m / min.
[0075] Furthermore, the flow rate L of the mixed gas is 15 L / min to 40 L / min. The diameter d of the optical fiber preform and the flow rate L of the mixed gas have the following relationship: L = k1 × d + k2, where d is in mm, k1 ranges from 0.3 to 0.6, and k2 ranges from 5 to 20. Maintaining this relationship between the diameter d of the optical fiber preform and the flow rate L of the mixed gas ensures the stability of the preform's crystal structure and prevents the formation of any other abnormal structural products.
[0076] It is understood that the melting temperature can be 1700℃, 1750℃, 1800℃, 1850℃, 1900℃, 1950℃, 2000℃, 2050℃, 2100℃, 2150℃, 2200℃, etc., but is not limited to the values listed above. Other values not listed within this range are also within the scope of protection of this application.
[0077] It is understood that the flow rate L of the mixed gas can be 15L / min, 16L / min, 17L / min, 18L / min, 19L / min, 20L / min, 21L / min, 22L / min, 23L / min, 24L / min, 25L / min, 26L / min, 27L / min, 28L / min, 29L / min, 30L / min, 31L / min, 32L / min, 33L / min, 34L / min, 35L / min, 36L / min, 37L / min, 38L / min, 39L / min, 40L / min, etc., but is not limited to the values listed above. Other unlisted values within this range are also within the scope of protection of this application.
[0078] It is understood that the value of k1 can be 0.3, 0.4, 0.5, 0.6, etc., but is not limited to the values listed above. Other unlisted values within this range are also within the scope of protection of this application.
[0079] It is understood that the value of k2 can be 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, etc., but is not limited to the values listed above. Other unlisted values within this range are also within the scope of protection of this application.
[0080] For steps S3 and S4, after the fiber transition body leaves the molten environment, the surface of the fiber transition body is vertically heated to ensure that the surface temperature T1 of the fiber transition body is 100℃ to 350℃.
[0081] Along the drawing direction of optical fiber 100, the optical fiber transition body undergoes vertical surface heating in a closed, vertical heating space with a length of 2m to 6m. The temperature of this heating space is linearly distributed within the range of 950℃ to 1200℃, and the temperature at the exit side of the heating space is higher than that at the inlet side, ensuring that the surface temperature T1 of the optical fiber transition body is 100℃ to 350℃ before leaving the heating space and before the coating operation. Subsequently, the optical fiber transition body, after vertical surface heating, is sent to a coating cup for coating with the aforementioned polyacrylate material. The coating ambient temperature T2 is 25℃ to 75℃, and the viscosity of the coating material during coating is 1000cps to 3500cps.
[0082] It is worth noting that the temperature difference T3 between the surface temperature T1 of the optical fiber transition body and the coating environment temperature T2 of the coating operation is 50℃ to 200℃, ensuring that the coating can adhere to the surface of the optical fiber.
[0083] It is understood that the temperature of the heating space can be 950℃, 1000℃, 1050℃, 1100℃, 1150℃, 1200℃, etc., but is not limited to the values listed above. Other unlisted values within this range are also within the scope of protection of this application.
[0084] It is understood that the surface temperature T1 of the optical fiber transition body can be 100℃, 150℃, 200℃, 250℃, 300℃, 350℃, etc., but is not limited to the values listed above. Other values not listed within this range are also within the scope of protection of this application.
[0085] It is understood that the coating environment temperature T2 can be 25℃, 30℃, 35℃, 40℃, 45℃, 50℃, 55℃, 60℃, 65℃, 70℃, 75℃, etc., but is not limited to the values listed above. Other values not listed within this range are also within the scope of protection of this application.
[0086] It is understood that the temperature difference T3 can be 50℃, 100℃, 150℃, 200℃, etc., but is not limited to the values listed above. Other unlisted values within this range are also within the scope of protection of this application.
[0087] In step S5, the outer periphery of the optical fiber transition body is coated and then sent to a curing device for coating curing to obtain optical fiber 100. Coating curing can be performed using either UV curing or LED curing. The curing environment is isolated using a non-oxygen gas, specifically nitrogen, helium, or argon, or a mixture of these in any proportion. The gas flow rate of a single curing oven is 15L to 30L, and the oxygen content in the curing environment is less than 50ppm. During the curing process, the optical fiber 100 must not be exposed to air for more than 0.04 seconds when passing through different curing ovens. After curing in the curing oven, the curing degree of the inner coating 31 of the optical fiber 100 is 87% to 92%, and the curing degree of the outer coating 32 is 90% to 100%, with the curing degree of the outer coating 32 not being less than that of the inner coating 31.
[0088] It is understood that the degree of curing of the inner coating 31 can be 87%, 88%, 89%, 90%, 91%, 92%, etc., but is not limited to the values listed above. Other values not listed within this range are also within the scope of protection of this application.
[0089] It is understood that the degree of curing of the outer coating 32 can be 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 100%, etc., but is not limited to the values listed above. Other values not listed within this range are also within the scope of protection of this application.
[0090] Example 1 An optical fiber preform with a diameter d of 150 mm is provided. The preform comprises, from the inside out, a core layer 10, a first transition layer 21, a second transition layer 22, multiple recessed layers 23, a third transition layer 24, and an outer cladding layer 25. The preform is fed into a drawing furnace for melting at a temperature of 2000℃. A mixture of argon and helium is used as the protective gas, with a flow rate L of 50 L. The mixture contains 60% argon and 40% helium, with an oxygen content of 90 ppm. The fiber drawing speed is 60 m / min.
[0091] Along the drawing direction of optical fiber 100, the fiber transition body formed after the melting process is subjected to vertical surface heating in a 5m heating space, with the temperature increasing from 1000℃ to 1200℃. Before the fiber transition body leaves the heating space for coating, its surface temperature T1 is 200℃. Subsequently, the fiber transition body, after vertical surface heating, is sent to a coating cup for coating with polyacrylate material. The coating environment temperature T2 is 50℃, and the viscosity of the coating material during coating is 2000 cps. The inner coating 31 has an elastic modulus of 0.6 MPa, a viscosity of 2000 mPa•s at 25°C, and a density of 1.1 g / cm³. 3 The elongation at break is 160%. The elastic modulus of the outer coating 32 is 780 MPa, the viscosity at 25°C is 5000 mPa•s, and the density is 1.2 g / cm³. 3 The elongation at break is 15%.
[0092] Subsequently, the outer periphery of the optical fiber transition body is coated and then sent to a curing device for coating curing to obtain optical fiber 100. UV curing is used for coating curing, and the curing environment is isolated using nitrogen. The gas flow rate of a single curing oven is 20L, and the oxygen content in the curing environment is 30ppm. During the curing process, the optical fiber 100 is exposed to air for 0.02 seconds as it passes through different curing ovens. After curing in the curing ovens, the curing degree of the inner coating 31 of the optical fiber 100 is 89%, and the curing degree of the outer coating 32 is 95%.
[0093] In the formed optical fiber 100, the core layer 10 has a radius of 4.5 μm, and the material composition of the core layer 10 is: SiO2:GeO2:F:K=98.3%:1.5%:0.1%:0.1%. The relative refractive index difference Δn1 of the core layer 10 is 0.4%.
[0094] The thickness of the first transition layer 21 is 3 μm, Δn2 is 0.2%, and Δn3 is 0.15%.
[0095] The material composition of the first transition layer 21 is as follows: SiO2:GeO2:F:K=99.68%:0.1%:0.12%:0.1%.
[0096] The thickness of the second transition layer 22 is 2.5 μm, Δn4 is -0.3%, and the material ratio of the second transition layer 22 at Δn4 is SiO2:F=99%:1%.
[0097] The first sunken layer 23a has a material composition of SiO2:F = 0.99:0.01 and a thickness of 5 μm. The second sunken layer 23b has a material composition of SiO2:F:GeO2 = 99.64%:0.3%:0.06% and a thickness of 6 μm. The third sunken layer 23c has a material composition of SiO2:F = 98.8%:1.2% and a thickness of 7 μm. Δn5 is -0.2%, and Δn6 is -0.3%.
[0098] The thickness of the third transition layer 24 is 3 μm, and the material ratio of the third transition layer 24 is SiO2:F=99%:1%.
[0099] The radius r8 corresponding to the outer periphery of the outer cladding layer 25 is 62 μm.
[0100] After testing, the dimensions of the formed optical fiber 100 are 180μm, the strength of optical fiber 100 is 150kpsi, the bending resistance of optical fiber 100 is 0.071dB at 1550nm with a radius of 5mm, and the transmission performance of optical fiber 100 is 0.189dB / km attenuation at 1550nm.
[0101] Example 2 The difference between this and Example 1 is that Δn2 is 0.2% and Δn3 is 0.2%.
[0102] After testing, the dimensions of the formed optical fiber 100 are 182μm, the strength of optical fiber 100 is 150kpsi, the bending resistance of optical fiber 100 is 0.073dB at 1550nm with a radius of 5mm, and the transmission performance of optical fiber 100 is 0.188dB / km attenuation at 1550nm.
[0103] Example 3 The difference between this and Example 1 is that Δn4 is -0.3% and Δn6 is -0.35%.
[0104] After testing, the dimensions of the formed optical fiber 100 are 181μm, the strength of optical fiber 100 is 150kpsi, the bending resistance of optical fiber 100 is 0.072dB at 1550nm with a radius of 5mm, and the transmission performance of optical fiber 100 is 0.188dB / km attenuation at 1550nm.
[0105] Comparative Example 1 The difference between this embodiment and Embodiment 1 is that the first transition layer 21 is not provided.
[0106] After testing, the dimensions of the formed optical fiber 100 are 181μm, the strength of optical fiber 100 is 100kpsi, the bending resistance of optical fiber 100 is 0.085dB at 1550nm with a radius of 5mm, and the transmission performance of optical fiber 100 is 0.189dB / km attenuation at 1550nm.
[0107] Comparative Example 2 The difference between this embodiment and Embodiment 1 is that the first transition layer 21 and the second transition layer 22 are not provided.
[0108] After testing, the dimensions of the formed optical fiber 100 are 186μm, the strength of optical fiber 100 is 100kpsi, the bending resistance of optical fiber 100 is 0.102dB at 1550nm with a radius of 5mm, and the transmission performance of optical fiber 100 is 0.195dB / km at 1550nm.
[0109] Comparative Example 3 The difference between this embodiment and Example 1 is that no third transition layer 24 is provided.
[0110] After testing, the dimensions of the formed optical fiber 100 are 183μm, the strength of optical fiber 100 is 100kpsi, the bending resistance of optical fiber 100 is 0.098dB at 1550nm with a radius of 5mm, and the transmission performance of optical fiber 100 is 0.192dB / km attenuation at 1550nm.
[0111] Comparative Example 4 The difference between this embodiment and Embodiment 1 is that a second recessed layer 23b is not provided.
[0112] After testing, the dimensions of the formed optical fiber 100 are 182μm, the strength of optical fiber 100 is 100kpsi, the bending resistance of optical fiber 100 is 0.112dB at 1550nm with a radius of 5mm, and the transmission performance of optical fiber 100 is 0.202dB / km attenuation at 1550nm.
[0113] Comparative Example 5 The difference between this embodiment and Embodiment 1 is that the first recessed layer 23a is not provided.
[0114] After testing, the dimensions of the formed optical fiber 100 are 182μm, the strength of optical fiber 100 is 100kpsi, the bending resistance of optical fiber 100 is 0.158dB at 1550nm with a radius of 5mm, and the transmission performance of optical fiber 100 is 0.211dB / km attenuation at 1550nm.
[0115] Comparative Example 6 The difference between this embodiment and Embodiment 1 is that a third recessed layer 23c is not provided.
[0116] After testing, the dimensions of the formed optical fiber 100 are 187μm, the strength of optical fiber 100 is 100kpsi, the bending resistance of optical fiber 100 is 0.168dB at 1550nm with a radius of 5mm, and the transmission performance of optical fiber 100 is 0.198dB / km at 1550nm.
[0117] Comparative Example 7 The difference between this and Example 1 is that the flow rate L of the mixed gas is adjusted to 100L, which means that the relationship between the diameter d of the optical fiber preform and the flow rate L is not satisfied.
[0118] After testing, the dimensions of the formed optical fiber 100 are 186μm, the strength of optical fiber 100 is 50kpsi, the bending resistance of optical fiber 100 is 0.076dB at 1550nm with a radius of 5mm, and the transmission performance of optical fiber 100 is 0.186dB / km attenuation at 1550nm.
[0119] Comparative Example 8 The difference between this and Example 1 is that T1 is 250°C and T2 is 35°C.
[0120] After testing, the dimensions of the formed optical fiber 100 are 168μm, the strength of optical fiber 100 is 50kpsi, the bending resistance of optical fiber 100 is 0.112dB at 1550nm with a radius of 5mm, and the transmission performance of optical fiber 100 is 0.196dB / km at 1550nm.
[0121] Comparative Example 9 The difference between this and Example 1 is that the temperature of the heating space increases from 800°C to 900°C.
[0122] After testing, the dimensions of the formed optical fiber 100 are 187μm, the strength of optical fiber 100 is 100kpsi, the bending resistance of optical fiber 100 is 0.088dB at 1550nm with a radius of 5mm, and the transmission performance of optical fiber 100 is 0.231dB / km attenuation at 1550nm.
[0123] Comparative Example 10 The difference between this and Example 1 is that the material ratio of the first sunken layer 23a is SiO2:F = 98.6%:1.4%.
[0124] After testing, the dimensions of the formed optical fiber 100 are 185μm, the strength of optical fiber 100 is 50kpsi, the bending resistance of optical fiber 100 is 0.056dB at 1550nm with a radius of 5mm, and the transmission performance of optical fiber 100 is 0.227dB / km attenuation at 1550nm.
[0125] Comparative Example 11 The difference between this and Example 1 is that the material ratio of the second sunken layer 23b is SiO2:F:GeO2=98.9%:0.9%:0.2%.
[0126] After testing, the dimensions of the formed optical fiber 100 are 186μm, the strength of optical fiber 100 is 50kpsi, the bending resistance of optical fiber 100 is 0.061dB at 1550nm with a radius of 5mm, and the transmission performance of optical fiber 100 is 0.224dB / km attenuation at 1550nm.
[0127] Comparative Example 12 The difference between this and Example 1 is that the material ratio of the third sunken layer 23c is SiO2:F = 98.2%:1.8%.
[0128] After testing, the dimensions of the formed optical fiber 100 are 185μm, the strength of optical fiber 100 is 50kpsi, the bending resistance of optical fiber 100 is 0.042dB at 1550nm with a radius of 5mm, and the transmission performance of optical fiber 100 is 0.241dB / km attenuation at 1550nm.
[0129] Comparative Example 13 The difference between this and Example 1 is that the material ratio of the first sunken layer 23a is SiO2:F = 99.7%:0.3%.
[0130] After testing, the dimensions of the formed fiber 100 are 186μm, the strength of fiber 100 is 150kpsi, the bending resistance of fiber 100 is 0.214dB at 1550nm with a radius of 5mm, and the transmission performance of fiber 100 is 0.187dB / km attenuation at 1550nm.
[0131] Comparative Example 14 The difference between this and Example 1 is that the material ratio of the second sunken layer 23b is SiO2:F:GeO2=99.88%:0.1%:0.02%.
[0132] After testing, the dimensions of the formed optical fiber 100 are 187μm, the strength of optical fiber 100 is 150kpsi, the bending resistance of optical fiber 100 is 0.249dB at 1550nm with a radius of 5mm, and the transmission performance of optical fiber 100 is 0.185dB / km attenuation at 1550nm.
[0133] Comparative Example 15 The difference between this and Example 1 is that the material ratio of the third sunken layer 23c is SiO2:F = 99.4%:0.6%.
[0134] After testing, the dimensions of the formed optical fiber 100 are 187μm, the strength of optical fiber 100 is 100kpsi, the bending resistance of optical fiber 100 is 0.201dB at 1550nm with a radius of 5mm, and the transmission performance of optical fiber 100 is 0.186dB / km attenuation at 1550nm.
[0135] The specific embodiments of this application have been described above with reference to the accompanying drawings. However, those skilled in the art will understand that various changes and substitutions can be made to the specific embodiments of this application without departing from the scope of this application. All such changes and substitutions fall within the scope defined by this application.
Claims
1. An optical fiber, characterized in that, It includes a core layer, a cladding layer, and a coating layer arranged sequentially from the inside to the outside. The cladding layer includes a first transition layer, a second transition layer, multiple recessed layers, a third transition layer, and an outer cladding layer arranged sequentially from the inside to the outside. The relative refractive index of the first transition layer near the core layer is set as Δn2, and the relative refractive index of the first transition layer near the second transition layer is set as Δn3, where Δn2 ≥ Δn3. The relative refractive index of the second transition layer decreases with increasing radius; The relative refractive index of the third transition layer increases with increasing radius.
2. The optical fiber as described in claim 1, characterized in that, The relative refractive index difference Δn1 of the core layer ranges from 0.28% to 0.6%. The numerical range of Δn2 is 0 to 0.25%, and the numerical range of Δn3 is 0% to 0.18%.
3. The optical fiber as described in claim 2, characterized in that, The core layer has a radius of 4 μm to 5.2 μm, the first transition layer has a thickness of 2 μm to 3.5 μm, the second transition layer has a thickness of 1.5 μm to 4.5 μm, and the third transition layer has a thickness of 2.5 μm to 4.5 μm.
4. The optical fiber as described in claim 2, characterized in that, The material composition of the core layer is as follows: SiO2:GeO2:F:K=(1-a1-b1-c1):a1:b1:c1, where the value of a1 ranges from 0.4% to 1.8%, the value of b1 ranges from 0.05% to 0.3%, and the value of c1 ranges from 0.05% to 0.2%. The material composition of the first transition layer is as follows: SiO2:GeO2:F:K=(1-a2-b2-c2):a2:b2:c2, where the value of a2 ranges from 0.08% to 0.15%, the value of b2 ranges from 0.05% to 0.15%, and the value of c2 ranges from 0 to 0.2%.
5. The optical fiber as described in claim 2, characterized in that, Multiple depression layers include a first depression layer, a second depression layer, and a third depression layer arranged sequentially from the inside out; The relative refractive index difference Δn4 of the first depressed layer ranges from -0.2% to -0.35%. The relative refractive index difference Δn5 of the second sunken layer ranges from -0.15% to -0.21%. The relative refractive index difference Δn6 of the third sunken layer ranges from -0.3% to -0.45%, and Δn6 ≤ Δn4.
6. The optical fiber as described in claim 5, characterized in that, The material ratio of the second transition layer at Δn4 is SiO2:F=(1-a3):a3, where the value of a3 ranges from 0.5% to 1.2%.
7. The optical fiber as described in claim 5, characterized in that, The thickness of the first sunken layer is 4.5 μm to 8 μm; the thickness of the second sunken layer is 3 μm to 6.5 μm; and the thickness of the third sunken layer is 4.2 μm to 9 μm.
8. The optical fiber as described in claim 1, characterized in that, The coating layer includes an inner coating layer and an outer coating layer arranged sequentially from the inside to the outside. The ratio of the thickness D1 of the inner coating layer to the thickness D2 of the outer coating layer is D1:D2 = (0.6 to 0.95):
1.
9. The optical fiber as described in claim 1, characterized in that, When the optical fiber size is 180μm, the strength of the optical fiber is ≥150kpsi, and when the bending radius of the optical fiber is 5mm, the bending loss at 1550nm is ≤0.1dB.
10. A method for fabricating optical fibers, characterized in that, The method for preparing the optical fiber as described in any one of claims 1 to 9 comprises the following steps: Provide an optical fiber preform corresponding to the optical fiber, the optical fiber preform comprising, from the inside out, a core layer, a first transition layer, a second transition layer, multiple recessed layers, a third transition layer and an outer cladding layer; The optical fiber preform is melted to form an optical fiber transition body; The surface of the optical fiber transition body is vertically heated to ensure that the surface temperature T1 of the optical fiber transition body is between 100°C and 350°C. The optical fiber transition body, after vertical surface heating, is coated. The temperature T2 of the coating environment is lower than the surface temperature T1 of the optical fiber transition body, and the difference between T2 and T1 is 50°C to 200°C. The coated fiber transition body is then cured to obtain the optical fiber.